Imigranci w polskiej przestrzeni wielkomiejskiej. Przypadek Poznania - Schmidt, Jacek (Człowiek i Społeczeństwo, 2014)
Immigrants make up only 2% of the total population in Poland. Over 80% of such immigrants reside in cities. Poland is only a transit point in their migration to the West or a temporary place of work or education. The paper focuses on the structure of the several-thousand, heterogeneous immigrant population in Poznań and the institutions within which they function and pursue their particular adaptation and integration strategies. Foreigners in Poznań live to some extent “next to” the receiving society and are hardly visible in the city space. Their migration is circular and often seasonal. A significant percentage is made up of the so called privileged migrants (students obliged to pay tuition fees at public and private universities and business professionals). Poznań, which is not a multicultural city, is not an important centre in the transnational network and can be defined as a typical “national” city based on local forms of socio-cultural relations.